2010
DOI: 10.1016/j.neulet.2009.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine enhances cell proliferation and decreases neurodegeneration in the hippocampus after transient global cerebral ischemia in rats

Abstract: This study was aimed to determine whether imipramine chronic treatment promotes neurogenesis in the dentate gyrus (DG) and interferes with neuronal death in the CA1 subfield of the hippocampus after transient global cerebral ischemia (TGCI) in rats. After TGCI, animals were treated with imipramine (20mg/kg, i.p.) or saline during 14 days. 5-Bromo-2'-deoxyuridine-5'-monophosphate (BrdU) was injected 24h after the last imipramine or saline injection to label proliferating cells. In order to confirm the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The meaning of this finding is still unknown. Imipramine and CBD presented protective effects under of different animal models of neurodegenerative conditions, such as brain ischemia (Pazos et al, 2012;Schiavon et al, 2010;Schiavon et al, 2014), Alzheimer's disease (Cheng et al, 2014), Parkinson's disease (LastresBecker et al, 2005), and schizophrenia (Gomes et al, 2015). The proneurogenic activity of CBD observed in the SVZ, therefore, might be related to its reparative and/or neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of this finding is still unknown. Imipramine and CBD presented protective effects under of different animal models of neurodegenerative conditions, such as brain ischemia (Pazos et al, 2012;Schiavon et al, 2010;Schiavon et al, 2014), Alzheimer's disease (Cheng et al, 2014), Parkinson's disease (LastresBecker et al, 2005), and schizophrenia (Gomes et al, 2015). The proneurogenic activity of CBD observed in the SVZ, therefore, might be related to its reparative and/or neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine also improved spatial cognitive performance, but not infarct volume. Imipramine administration for 2 weeks increased BrdU incorporation and survival of BrdU-labeled hippocampal cells in rats after transient forebrain ischemia [40]. In summary, current data permit no definitive conclusion regarding the ability of antidepressants to potentate ischemia-induced neurogenesis.…”
Section: Neurogenesismentioning
confidence: 67%
“…In the evaluation of histological analysis and MDA level, only slight preventive effect of imipramine against ischemic damage was observed by a single treatment with imipramine alone. On the other hand, recently imipramine was reported to be able to enhance the cell proliferation and protection by prolonged administration at once a day for 14 days after transient global cerebral ischemia (19 have been reported that imipramine alone can exert anti-inflammatory and neuroprotective effect in central nervous system and prevent directly ischemic damage (17). We surmised that different administration schedule and doses of imipramine employed in each study may contribute to these conflicting results, so in order to observe the neurogenetic and neuroprotective effects of imipramine, a longer time and higher concentrations might be required than those we used.…”
Section: Effect Of Imipramine On the Protective Activity Of Pep-1-catmentioning
confidence: 99%
“…It is recently reported that bulbectomy is a well-established depression animal model and leads to reduced cell proliferation in the hippocampal subgranular zone and the subventricular zone (SVZ), but subchronic administration of imipramine can restore neurogenesis in these regions (18). Also, it has suggested that chronic treatment of imipramine enhanced cell proliferation in the subgranular zone of dentate gyrus and re-http://bmbreports.org duced the neurodegeneration in the CA1 of the hippocampus 14 days after transient global cerebral ischemia in rats (19). In addition, imipramine is reported to markedly inhibit the inflammation in the carrageenan-induced paw edema model (20).…”
Section: Introductionmentioning
confidence: 99%